Incidence of late‐onset pneumonia in patients after treatment with radiotherapy for nasopharyngeal carcinoma: A nationwide population‐based study. Issue 12 (13th November 2014) - Yen, Ting‐Ting; Lin, Ching‐Heng; Jiang, Rong‐San; Shih, Yi‐Ting; Yen, Hung‐Rong; Liang, Kai‐Li
ABSTRACT: Background: The purpose of this study was to assess the incidence of late‐onset pneumonia in patients with nasopharyngeal carcinoma (NPC) after radiotherapy. Methods: Data were retrieved from the National Health Institute Research Database of Taiwan. We identified patients diagnosed with NPC (International Classification of Disease 9th revision‐Clinical Modification [ICD‐9‐CM] code 147) from January 2005 to December 2008 who received curative radiotherapy as the study cohort. Incidences of pneumonia and related sequelae after 90 days of radiotherapy were calculated. Results: A total of 3814 patients were enrolled in this study and 210 (5.5%) had late‐onset pneumonia. The correlation coefficient between pneumonia and tube feeding was 0.332 ( p  < .001). The hazard ratio of pneumonia was 0.81 (95% confidence interval [CI] = 0.57–1.15) between patients with and without chemotherapy, and was 2.37 (95% CI = 1.73–3.24) between patients with and without re‐radiation. Conclusion: Late‐onset pneumonia is not uncommon in patients with NPC after radiotherapy. The risks of associated sequelae and mortality cannot be ignored. © 2014 Wiley Periodicals, Inc. Head Neck 37: 1756–1761, 2015